Pemikiran Abdul Qadim Zallum tentang Majelis Umat dan Dewan Perwakilan Rakyat di Indonesia - Arifin, M. Syamsul (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article describes the conception of Majelis Umat according to Abdul Qadim Zallum and conception of the DPR under the Constitution of 1945. In Abdul Qadim Zallums thought, the conception of Majelis Umat and the DPR basically is a representative of the people in each form of the state, but in conception of Majelis Umat the representativeness of race is limited, such as in the establishment of the law, a people representative of the non-Muslims cant contribute to the perfection of the law because they are not representative for analizyng Islamic law, so is the Majelis Umat in his opinion (most votes) is not binding for the Caliph, with other words Majelis Umat dont have any authority in law as having law is God. In the conception of DPR, any issues relating to the welfare of the people being their authority, certainly not without the approval of the President as the leader of the government. So the differences that really stands out is the authority of the Majelis Umat who are severely restricted by the Caliph and shari'ah law itself. While in DPR based on the Constitution of 1945, as long as not contrary to the basis of the country, DPR has the right to request the approval of the President. Keywords: Majelis Umat, the conception, DPR, Abdul Qadim Zallum